Certificate of extension of special-tax stamp no. V175350, 1891 (1891)
Receipt of a special tax paid by Ah Louis' business as a 'retail liquor dealer'. The text of the document reads: 'The sum of Four Dollars Sixteen and Two-thirds Cents having this day been paid to me by Ah Louis for special tax on the business of Retail Liquor Dealer, to be carried on at San Luis Obispo, state of Cal., for the months of May and June, 1891, Special-Tax Stamp No. V175350, issued to ______, covering the business ad place of business above mentioned to April 30, 1891, is hereby extended to June 30, 1891.'